Minimal risk of Rabies lyssavirus spillover from bats in Israel: findings from long-term surveillance - Weinberg, Maya; King, Roni; Lapid, Roi; Yakobson, Boris; Eyngor, Marina; Luo, Dongsheng; Giotis, Efstathios S. (Frontiers in Microbiology, 2025)
Rabies, caused by viruses of the genus Lyssavirus (family Rhabdoviridae), remains a persistent public health and veterinary challenge in Israel, a small but strategically positioned country at the crossroads of Africa, Asia, and Europe. Over the past 18 years (2006–2024), more than 670 confirmed rabies cases have been reported in humans, wildlife, farm animals, and stray dogs, with the latest human fatality recorded in November 2024, following a bite from an unvaccinated dog. While domestic dogs (Canis familiaris) and golden jackals (Canis aureus) account for the majority of cases, little is known about the role of Israel’s 32 bat species in the circulation of Lyssavirus rabies. We analyzed national rabies testing records spanning nearly three decades (1995–2022), encompassing over 42,000 animals. Among the 294 bats tested, representing both insectivorous and frugivorous species, none were positive for rabies virus (R. lyssavirus; RABV). These findings contrast sharply with the high prevalence detected in carnivores and livestock and align with the absence of documented bat-to-human transmission events in Israel. These results suggest that bats in Israel remain largely isolated from the Lyssavirus transmission cycles affecting other domestic and wild mammals and may pose minimal risk for rabies or other Lyssavirus spillover in the region. They also underscore the significance of sustained long-term surveillance to detect emerging Lyssavirus threats.